STRATEGI PEMASARAN PADA MASA COVID-19 DALAM MENINGKATKAN PENJUALAN PADA SHOWROOM ABADI MOTOR KENDARI - Fatimah Fatimah; Rahmat Madjid; Alida Palilati; Muhammad Rivan Kohawan; Rahmat Rialdy Hasan (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2023)
This study aims to find out how the marketing strategy during the Covid-19 era was in increasing sales at the Abadi Motor Kendari Showroom. The informants of this study were the owner of the Abadi Motor Kendari Showroom, operational and marketing fields with primary data sources, namely internal data from the Abadi Motor Kendari Showroom such as sales data, number of employees, organizational structure and others. The data analysis technique used by the author is a qualitative descriptive data analysis technique, namely research that uses data that is stated verbally and its qualifications are theoretical. The results of the study indicate that the marketing strategy used at the Abadi Motor Kendari Showroom is differentiation, the strategy seeks to expand/add types of business and improve services through the use of strengths in the form of the variety of products needed, the number and variety of products, quality, flexibility, cost reduction and delivery, the existence of a policy higher prices, intensive promotion and operational activities to seize the opportunities that exist in the form of growing community education